Le statut paradigmatique du langage chez Vygotski. Aspect méthodologique du problème - Boutchilina Nesselrode, Ludmila (Rivista Italiana di Filosofia del Linguaggio, 2012)
This article develops a problem of paradigmatic classification of Vygotsky's language conception. His psychological studies cannot be interpreted one-sidedly: it is as much naturalistic as sociological. This is a paradox which is quite rare in the history of science. His heterogenous perspective for development of social to the personal via biologic opposes Piaget's linear study. The question is where we can find the naturalistic source of Vygotsky's language concept. We have to goals. First is to study methodological aspects of the Vygotsky's naturalistic notion of social relationships. Second is to look at this subject in author's so called historical approach to the bio-sociological unity of thinking process and language as well as an individual and his environment. Our study is divided in two parts. Firstly, we relate Vygotsky's thesis with Darwin's antithese principle. Vygotsky himself refers to it when introducing the idea of individual into the study of social. Then we discover the operational block of Vygotsky's analysis, where he insists on the following: 1) a certain ratio of a general and a particular when dealing with science and clinical data; 2) resolving analysis of psycho-, socio- and linguistic entities; 3) 4-part dialectic method for the resolution of psychological processes. Thus we find the hypothesis that the naturalistic source of Vygotsky's studies lays in Darwinian antithesis principle. Vygotsky develops it as a conflict situation. He reconstructs the contradiction between a nature and a culture to find all possible ways of its productive resolution